2022
DOI: 10.1038/s41531-022-00350-7
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal modulation of subthalamic beta oscillatory power in Parkinson’s disease patients during deep brain stimulation

Abstract: Beta-band activity in the subthalamic local field potential (LFP) is correlated with Parkinson’s disease (PD) symptom severity and is the therapeutic target of deep brain stimulation (DBS). While beta fluctuations in PD patients are well characterized on shorter timescales, it is not known how beta activity evolves around the diurnal cycle, outside a clinical setting. Here, we obtained chronic recordings (34 ± 13 days) of subthalamic beta power in PD patients implanted with the Percept DBS device during high-f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 48 publications
1
64
0
Order By: Relevance
“…Second, we observed medication-related changes of the aperiodic exponent in hemispheres without clear beta peaks or medication-related beta changes. Third, we estimate the aperiodic exponent between 40 and 90 Hz, when studying the effect of levodopa, avoiding lower frequencies, which are particularly susceptible to movement-related artefacts (van Rheede et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we observed medication-related changes of the aperiodic exponent in hemispheres without clear beta peaks or medication-related beta changes. Third, we estimate the aperiodic exponent between 40 and 90 Hz, when studying the effect of levodopa, avoiding lower frequencies, which are particularly susceptible to movement-related artefacts (van Rheede et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic sensing was set up as previously described. 9 In one case (sub-014) sensing was activated only in the right hemisphere. This has led to the availability of brain signal recordings from seven STNs in 4 patients, with a mean peak frequency of 18.8 AE 6 Hz.…”
Section: Data Acquisitionmentioning
confidence: 97%
“…All participants provided written informed consent. 9 The study was approved by the local ethics committee of the Charité -Universitätsmedizin Berlin (EA2/256/ 60) and conducted in accordance with the ethical standards set by the Declaration of Helsinki. The inclusion criterion for the retrospective study was the availability of at least 22 days of chronic brain signal recordings starting from December 10 to January 1.…”
Section: Participantsmentioning
confidence: 99%
“…In the US, EU and Canada the ADAPT PD approval trial (NCT04547712) evaluating aDBS has completed enrollment. In Japan, where aDBS is approved, early case study results are promising (Nakajima et al, 2021;Kimura et al, 2022;van Rheede et al, 2022) and continue to build upon the evidence for patient benefit suggested by previous investigational pilots (Little et al, 2013;Arlotti et al, 2018;Velisar et al, 2019). Finally, several physiciansponsored NIH BRAIN Initiative trials are applying the Summit TM RC + S to investigate new indications including treatment resistant depression, Tourette's syndrome and opioid use disorder.…”
Section: Utilizing Brainsense Technology To Guide Dbs Therapymentioning
confidence: 99%
“…Moreover, studies across multiple centers demonstrate the capability of Percept ™ PC to routinely detect LFP signals of interest in PD, ET, dystonia, OCD and epilepsy subjects with standard of care procedures ( Fasano et al, 2021 ; Goyal et al, 2021 ; Thenaisie et al, 2021 ; Buijink et al, 2022 ; Vissani et al, 2022 ), which is also consistent with prior studies using investigational recording devices ( Case et al, 2020 ; Darcy et al, 2022 ). Further, there is a growing body of case studies demonstrating the application of brain sensing for personalized treatment including initial DBS programming ( Fasano et al, 2021 ; Sirica et al, 2021 ), DBS and medication optimization ( Kern et al, 2022 ), and even understanding circadian patterns ( van Rheede et al, 2022 ).…”
Section: Cutting Edge Technologies From the Industry Sectormentioning
confidence: 99%